Production and characterization of cellulases and xylanases from the thermophilic ascomycete Thielavia terrestris 255B. - Gilbert, Michel. (University of Ottawa (Canada), 1992)
Initially, we studied the production of cellulases and xylanases after growth of T. terrestris 255B on various substrates in order to obtain maximum production of these enzymes. We used non-denaturing electrophoretic techniques to compare the profile of enzymes produced on the various substrates. We found that T. terrestris 255B produced two major and at least 5 minor endoglucanase components. We discussed the possibility that some of these components might exist as multi-enzyme complexes that were difficult to isolate in an intact form. We purified two cellobiohydrolases and one $\beta$-glucosidase which were all partially characterized. One of the cellobiohydrolases (CBHII) seemed to be a major component of the cellulase system as it accounted for about 40.8% of the observed activity when crystalline cellulose was used as the substrate. T. terrestris 255B produced two major forms of xylanases with pI's of 4.6 (xylanase I) and 6.1 (xylanase II). The latter enzyme could be purified to $>$99% homogeneity using anion-exchange chromatography and gel filtration. Xylanase II had a molecular mass of 25.7 kDa (SDS-PAGE) and optimal pH and temperature of 3.6-4.0 and 60-65$\sp\circ$C, respectively. The activity of xylanase II was very specific towards the hydrolysis of xylan and had extremely low activity on cellulose. Thus, as it had potential application for the pre-bleaching of kraft pulps, the characterization of this enzyme became the main focus of the work. We used amino acid composition and partial amino acid sequencing to demonstrate that xylanase II belonged to a family of low molecular weight xylanases which had been previously designated the G family by Gilkes et al. (1991b). Currently, xylanase II is the only thermophilic xylanase that has been shown to belong to the G family of $\beta$-1,4-glycanases. Xylanase II has one disulfide bridge and it is possible that this might account for its higher thermostability when compared to the other members of the G family. We studied the mode of action of xylanase II and compared it with a 32-kDa xylanase derived from Thermoascus crustaceus. This latter enzyme is a thermophilic xylanase which appears to belong to the F family of $\beta$-1,4-glucanases. Xylanase II was more efficient at solubilizing insoluble xylan and yielded hydrolysis products with higher degrees of polymerization than the 32-kDa xylanase. Xylanase II could not cleave xylotriose although it cleaved xylotetraose to xylobiose and xylotriose using a process involving transxylosidation. The 32-kDa xylanase could cleave both xylotriose and xylotetraose to xylobiose and xylose. Xylose was a major product of xylan hydrolysis by the 32-kDa xylanase while it was only a minor product when the hydrolysis was performed with xylanase II. Although xylanase II and the 32-kDa xylanase seem to belong to different families of xylanases and had different modes of action, they did not show any cooperative hydrolysis action when they were added to xylans from various sources (cereal, hardwoods and softwoods). The profile of products obtained when the two thermophilic xylanases were used together was almost identical to the profile obtained when the 32-kDa xylanase acted alone. (Abstract shortened by UMI.)
Keywords: Chemistry, Biochemistry.